2011
DOI: 10.1177/0956797611419302
|View full text |Cite
|
Sign up to set email alerts
|

Pop-Out Without Awareness

Abstract: Visual “pop-out” occurs when a unique visual target (e.g. a feature singleton) is present among a set of homogeneous distractors. However, the role of visual awareness in this process remains unclear. Here we show that, even though subjects were not aware of a suppressed pop-out display, their subsequent performance on an orientation discrimination task was significantly better at the pop-out location than at a control location. These results indicate that visual awareness of a feature singleton is not necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 45 publications
(65 reference statements)
4
38
0
Order By: Relevance
“…It has been shown that a simple and salient stimulus could attract one’s attention unconsciously: a feature singleton (i.e. Gabor patch) is able to attract attention when presented alone24 or in a set of homogeneous distractors, namely an unconscious pop-out effect2526. Our Experiment 3, on the other hand, demonstrated feature-integration-driven attention could come into play even when the stimulus was well suppressed and wiped out from conscious awareness.…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that a simple and salient stimulus could attract one’s attention unconsciously: a feature singleton (i.e. Gabor patch) is able to attract attention when presented alone24 or in a set of homogeneous distractors, namely an unconscious pop-out effect2526. Our Experiment 3, on the other hand, demonstrated feature-integration-driven attention could come into play even when the stimulus was well suppressed and wiped out from conscious awareness.…”
Section: Discussionmentioning
confidence: 55%
“…We used this approach (in all but one experiment) to determine whether color singleton cues as well as single cues enhance contrast sensitivity. In contrast, previous studies on capture by singletons often present the target in a field of distractors (exceptions: Hsieh, Colas & Kanwisher, 2011; Kim & Cave, 1999; Theeuwes et al, 2004), and with much spatial uncertainty regarding the target’s location.…”
mentioning
confidence: 76%
“…Several studies report that just after the appearance of a color or orientation singleton, responses are speeded to subsequent targets near the singleton and slowed to more distant targets (Burnham & Neely, 2008; Donk & Soesman, 2010; Folk et al, 1992; Kim & Cave, 1999; Mounts, 2000b). Discrimination accuracy is also higher at the singleton’s location than others (Joseph & Optican, 1996; Hsieh, Colas & Kanwisher, 2011; Mounts, 2000a; Theeuwes & Chen, 2005), and higher when there is no distracting singleton present compared with when there is one far from the target (Caputo & Guerra, 1998; Folk, Leber & Egeth, 2002; Theeuwes, Kramer & Kingstone, 2004). …”
mentioning
confidence: 91%
“…Attentional capture has recently been demonstrated to operate not as an all-ornone process but rather more gradually, with capture strength increasing with cue contrast (Fuller et al, 2009;Zehetleitner et al, 2013). Another body of work suggests that attentional capture can be modulated through top-down factors such as task set (Ansorge et al, 2011;Folk et al, 1992;Hsieh et al, 2011). The present results demonstrate an additional determinant of capture strength Table 1 Results of stepwise modeling of cue visibility reports as a function of cue type (control vs. phosphenes, phosphenes vs. real cues) and cue validity (valid vs. invalid), together with degrees of freedom per model and goodness-of-fit parameters (AIC, BIC, and G 2 ) of the models.…”
Section: Discussionmentioning
confidence: 97%